Differential flight responses of spring staging Teal Anas crecca and Wigeon A. penelope to human versus natural disturbance - Bregnballe, Thomas; Speich, Charlotte; Horsten, Anders; Fox, Anthony D. (Wildfowl, 2017)
Observations made of disturbance to spring staging Wigeon Anas penelope and Teal A. crecca by human and â€œnaturalâ€ (non-human) stimuli at a restored wetland in the Skjern River delta, Denmark, were analysed to inform future management of human access to the site. The effects of human activity (anglers, cyclists, farming activity) on the flight responses and displacement distances of ducks within uniform habitat along a public path were compared with the birdsâ€™ reaction to natural stimuli such as mammals or birds of prey. Excluding the controlled disturbance by a pedestrian, undertaken as part of the study, the main cause of flushing in Wigeon was a response to the movements of birds of prey and other birds, especially Lapwings Vanellus vanellus performing flight displays. For Teal, birds of prey accounted for around half of the flushes, with other birds accounting for one third of the flushes. Wigeon and Teal were displaced significantly farther by human activities than by natural causes. We tested whether the ducks reacted differently to natural disturbances shortly after disturbance by a pedestrian by comparing response patterns to natural stimuli within the first hour following disturbance from a passing pedestrian with their response patterns in the absence of pedestrians, but found no evidence to suggest that they did so. In our study area, Wigeon used land for feeding and water as predator-escape habitat; 23% of the 144 observed take-offs of Wigeon were from water but 68% of the landings were on water. Of the 83 observations of flushed Teal, 56% flushed from water and 51% landed on water.